Photocatalytic degradation of methylene blue by nanostructured Fe/FeS powder under visible light - Esmaili, Hassan; Kotobi, Amir; Sheibani, Saeed; Rashchi, Fereshteh (International journal of minerals, metallurgy and materials, 2018)
The photocatalytic performance of mechano-thermally synthesized Fe/FeS nanostructures formed from micron-sized starting materials was compared with that of a thermally synthesized nanostructure with nano-sized precursors in this paper. The properties of as-synthesized materials were studied by X-ray diffraction（XRD）, transmission electron microscopy（TEM）, vibrating sample magnetometry（VSM）, diffuse reflectance spectroscopy（DRS）, and ultraviolet–visible（UV-Vis） spectroscopy. The effects of irradiation time, methylene blue（MB） concentration, catalyst dosage, and p H value upon the degradation of MB were studied. Magnetic properties of the samples showed that both as-synthesized Fe/FeS photocatalysts are magnetically recoverable, eliminating the need for conventional filtration steps. Degradation of 5 ppm of the MB solution by mechano-thermally synthesized Fe/FeS with a photocatalyst dosage of 1 kg/m~3 at pH 11 can reach 96% after 12 ks irradiation under visible light. The photocatalytic efficiency is higher in alkaline solution. The kinetics of photocatalytic degradation in both samples is controlled by a first-order reaction. However, the rate-constant value in the thermally synthesized Fe/FeS photocatalyst sample is only 1.5 times greater than that of the mechano-thermally synthesized one.